Inter-rater Reliability and Construct Validity of the Lerner Defense Scale in Clinical and Non-clinical Groups - Rosso, Anna Maria; Airaldi, Cinzia; Camoirano, Andrea (Frontiers in Psychology, 2021)
The current study investigated the validity and the inter-rater reliability of the Rorschach Lerner Defense Scale (LDS). In particular, it aimed to investigate the ability of the scale to distinguish between neurotic level and borderline level personality organization, according to Psychodynamic Diagnostic Manual-2, and non-clinical subjects, and to explore the inter-rater reliability, analyzing the most frequent coding mistakes in order to possibly improve the coding guidelines. Eighty clinical subjects and 80 non-clinical ones participated in the study. Among the clinical subjects, 40 have borderline level personality organization and 40 have neurotic level personality organization. Nonclinical subjects were drawn from an archival dataset of nonclinical individuals who previously participated in a Rorschach normative study. LDS distinguished borderline level subjects from both the nonclinical and neurotic groups with regard to Devaluation and Projective Identification, with borderline level personality organization subjects reporting higher scores than both of the other groups. Only Denial scale discriminated between nonclinical and neurotic group, with the latter reporting higher scores. LDS showed substantial inter-rater reliability, however guidelines could be improved. Specifically, they should be improved with regard to the threshold for coding Devaluation and Idealization at level 1. Furthermore, more examples should be included in the manual about the coding of Projective Identification and Denial.